Analisa Potensi Penggunaan PLTS On Grid di Kota Makasar - Simon Patabang; Limbran Sampebatu; Aries Kamolan (Jurnal Ampere, 2023)
Makassar is the center of government and business center in the province of South Sulawesi. The people of Makassar has a very high dependence on the use of electrical energy to meet their daily needs, both at home and at offices. The use of electrical energy which is quite high will cause an increase in customer bills every month. Therefore, this problem needs to be reduced by utilizing alternative energy sources. PLTS on grid is one of the solutions to reduce dependence on electrical energy from PLN. This research was carried out using a load simulation method based on the level of solar radiation in Makassar City at an installed power of 4500 VA. By using PLTS on grid the customer has two sources of electrical energy, from solar power and PLN line. The main source of electrical energy during the day is from on grid solar power and at night is from PLN line. If the power from the on grid solar power the day is insufficient to serve the load needs, PLN will automatically responsible for the electric power of the load. The simulation results show that the use of on-grid PLTS saves PLN's electricity consumption by 34.78% to 89.53%. These results illustrate that the potential for using on grid solar panels in the city of Makassar is very large